2019
DOI: 10.1177/0091552119864409
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency for Whom? Varying Impact of Performance-Based Funding on Community Colleges in Louisiana

Abstract: Objective: This study examines whether Louisiana’s performance-based funding (PBF) implementation in 2011 impacts various academic outcomes at community colleges, and whether the impact varies for institutions with higher proportions of underrepresented students. Method: Using institutional-level panel data between 2006 and 2016, I employ difference-in-differences to estimate the average treatment effect of the Granting Resources and Autonomies for Diplomas (GRAD) Act on credential production, retention, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Several quasi-experimental studies have employed a DD regression approach and shown that PBF can lead to increases in the production of short-term certificates rather than associate degrees (Hillman et al, 2015, 2018; Hu, 2019; Li & Kennedy, 2018; Li & Ortagus, 2019). Hillman et al (2018) examined two of the most robust PBF-participating states, Tennessee and Ohio, and found that Tennessee community colleges responded to PBF by producing more certificates rather than longer-term associate or bachelor’s degrees.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several quasi-experimental studies have employed a DD regression approach and shown that PBF can lead to increases in the production of short-term certificates rather than associate degrees (Hillman et al, 2015, 2018; Hu, 2019; Li & Kennedy, 2018; Li & Ortagus, 2019). Hillman et al (2018) examined two of the most robust PBF-participating states, Tennessee and Ohio, and found that Tennessee community colleges responded to PBF by producing more certificates rather than longer-term associate or bachelor’s degrees.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
“…In an earlier study, Hillman et al (2015) explored the influence of PBF adoption in the state of Washington, finding that community colleges did not improve degree completion but instead increased the production of short-term certificates. In examining Washington’s PBF policy, Hu (2019) found an increase in certificate production and graduation rates but no change in associate’s degree production. These four studies, all of which meet our established criteria for providing strong causal evidence regarding the impacts of PBF, indicate that institutions respond to PBF by improving shorter-term outcomes (e.g., certificate production) at the expense of longer-term outcomes (e.g., associate degree production).…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
“…In other words, within states that have a PF policy, colleges will act in ways aimed at improving performance because colleges are provided material incentives from the state (Dougherty and Hong 2006 ; Dougherty and Reddy 2013 ). Studies incorporating a resource dependency perspective typically suggest that colleges that rely more heavily on state appropriations (such as community colleges) will be more likely to engage in the desired behaviors of improving stated student outcomes (Hu 2019 ; Li and Ortagus 2019 ).…”
Section: Theoretical Logic Of Performance Fundingmentioning
confidence: 99%
“…Hu ( 2019 ) examined PF in Louisiana and divided her dataset using the proportion of racially minoritized students at each institution. She designated each institution as a minority-serving institution (MSI) using a 25% enrollment cutoff of that particular group and a 50% enrollment threshold for all minorities combined.…”
Section: Policy Evaluationmentioning
confidence: 99%
See 1 more Smart Citation